DISCOUNT RATE IN THE ENTERPRISE BUSINESSES AND PROJECTS ASSESSMENT - Molina A., Hércules (2004)
This article presents the major criteria for using a discount rate in business plans and investment projects, out of the analysis and comparison of the problems arising in emerging and incomplete capital markets, by means of using the Capital Assets Price Assignment Classic Model (CAPM), with the aim of getting more accurate results as for parameters appraisal.